Magnetic graphene oxide increases the biocompatibility and nuclear factor erythroid 2-related factor 2 antioxidant of human cumulus cells: A lab-trial study - Fahimeh Kabiri; Tahereh Foroutan; Maryam Pashaiasl (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Although assisted reproductive technology has been improved, the success rate is only 30%. Since the interaction between oocytes and cumulus cells (CCs) is necessary for the formation of a fertile oocyte, increasing the survival rate of CCs can improve the function of oocytes in infertile women. Objective: This study aimed to investigate the effects of magnetic graphene oxide (MGO) nanocomposite on the biocompatibility and antioxidant activity of human CCs. Materials and Methods: In this lab-trial study, from July 2021-2023 human CCs were collected from 37 women aged 20-37 yr and cultured in a medium containing Dulbecco's Modified Eagle's/F12, fetal bovine serum (10%), and penicillin-streptomycin (1%). Then CCs were treated with increasing concentrations of nano-MGO for 24, 48, and 72 hr (3[4, 5-dimethylthiazole-2-yl]-2, 5-diphenyltetrazolium bromide) assay and flow cytometry technique were used to compare the survival rate and apoptosis of CCs before and after treatment. Western blot test was used for expressing nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant in 2 groups. Results: The results of the present study showed that treatment with MGO increased the viability of CCs at a concentration of 50 µg/ml after 48 hr (p > 0.01). At higher doses (100 µg/ml) MGO decreased the survival rate of CCs (p > 0.05). Also, treatment with MGO at a concentration of 50 µg/ml increased the expression level of antioxidant protein Nrf2 in human CCs. Conclusion: Our results highlight the use of MGO in a new strategy that improves CCs viability and secretion of antioxidant protein Nrf2, thereby potentially increasing in vitro fertilization outcomes.